Algorithmic combinatorics : enumerative combinatorics, special functions and computer algebra : in honour of Peter Paule on his 60th birthday /: enumerative combinatorics, special functions and computer algebra : in honour of Peter Paule on his 60th birthday. ([2020]) - Unknown
No abstract available